2015
DOI: 10.1103/physreve.91.043306
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-relaxation-time lattice Boltzmann kinetic model for combustion

Abstract: To probe both the Hydrodynamic Non-Equilibrium (HNE) and Thermodynamic NonEquilibrium (TNE) in the combustion process, a two-dimensional Multiple-Relaxation-Time (MRT) version of Lattice Boltzmann Kinetic Model(LBKM) for combustion phenomena is presented. The chemical energy released in the progress of combustion is dynamically coupled into the system by adding a chemical term to the LB kinetic equation. Beside describing the evolutions of the conserved quantities, the density, momentum and energy, which are w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 81 publications
(140 reference statements)
1
109
0
1
Order By: Relevance
“…Generally, the nonequilibrium state is too complex to be described. Fortunately, the DBM provides an effective tool to investigate the nonequilibrium manifestations [10,11,[46][47][48][49]. It is noteworthy that f (5)- (7) according to the conservation of mass, momentum and energy.…”
Section: B Nonequilibrium Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the nonequilibrium state is too complex to be described. Fortunately, the DBM provides an effective tool to investigate the nonequilibrium manifestations [10,11,[46][47][48][49]. It is noteworthy that f (5)- (7) according to the conservation of mass, momentum and energy.…”
Section: B Nonequilibrium Manifestationsmentioning
confidence: 99%
“…7 (not shown here). Furthermore, the nonequilibrium quantities are not susceptible to numerical errors in the discretization and evolution of the DBM [47,49] differences are 4% and 13% , respectively. This is satisfactory.…”
Section: Figs 5 (C) (D) (G) and (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…When x f = d/2, q = 0, f = p/2, and y f ' = 0 which, when combined with Eqs. (7), (8), and (9), yield:…”
Section: Mathematical Model and Analysis Processmentioning
confidence: 99%
“…Tran [6] et al found that a detonation wave is closely related to charge diameter and density through experiment and the confinement material can affect the detonation velocity and shock front curvature. In recent years a discrete Boltzmann model, or lattice Boltzmann kinetic model, was proposed to investigate the nonequilibrium effects in combustion systems, especially in micro-channel explosion systems [7][8][9][10]. Further, much numerical simulation work has been done on detonation wave propagation to study the diameter effect.…”
Section: Introductionmentioning
confidence: 99%